Dietary Intake and Cognitive Developmental Outcomes of Children Below Five Years Living with Special Needs in Kakamega County: A Baseline Survey - Lucy Amanya Mutuli (International Journal of Nutrition, 2026)
In early childhood, adequate dietary intake is essential for optimal growth, brain development, and the acquisition of cognitive skills. However, children with special needs often face increased nutritional vulnerability due to feeding difficulties, restricted diets, metabolic anomalies and limited access to health and care services. These challenges significantly compromise their access to optimal dietary intake that negatively impacts on their cognitive development and functioning. This baseline survey aimed at identifying the existing characteristics of dietary intake and cognitive developmental outcomes of children aged below five years with special needs in Kakamega County. We involved 90 mother/child caregiver-child pair, selected through stratified sampling from early childhood development centers in Kakamega County. Data was collected using 24-hour dietary recall, food frequency questionnaires, anthropometric and Bayley Scales of Infant and Toddler Development (BSIDIV) was used for assessment of cognitive development outcomes. Findings revealed high levels of micronutrient deficiencies, with 66.7 percent not meeting recommended intake for vitamin A, 76.7 percent for iron, and 89 percent for zinc. Only 47.7 percent met minimum dietary diversity score. Nutrition assessments showed 52.2 percent of children had normal weight and 6.7 percent were severely undernourished. Feeding dependence varied by disability with 100 percent of children with ADHD self-fed. Cognitive assessments showed that children with physical disabilities had the highest scores across all cognitive domains, while children with autism demonstrated lowest, particularly in communication and executive functioning. In conclusion, the prevalence of nutritional deficiencies as a consequence of sub-optimal dietary intake, particularly in essential micronutrients are closely linked to poor cognitive developmental outcomes. Low levels of nutrition education of parents and feeding dependency negatively impacts on cognitive development outcomes of children with special needs. Thus, implementation of special needs inclusive of nutrition interventions, caregivers’ training and early stimulation programs to support holistic development of these children is needed.
Keywords: Dietary intake